(untitled) (Sciences & Technology. A, exactes sciences, 2014)
The degradation of isoproturon 3-(4-isopropylphenyl)-1,1dimethylurea photoinduced by Fe(III) in aqueous solution has been investigated. The rate of degradation depends on the concentration of Fe(OH)2+, the most photoreactive species in terms of .OH radical formation. These .OH radicals are able to degrade isoproturon until total mineralisation. The formation of Fe(II) in the irradiated solution was monitored. The sonophotochemical degradation of isoproturon has been found to be dependent on the intensity of sonication. The combination of ultrasound and photochemistry has been used to degrade an aqueous solution of Isoproturon (IP). The degradation of IP in aqueous solution was investigated under sonolysis at 500 kHz and in the presence of Fe(III), as well as under simultaneous sonolysis and photoinduced Fe(III). Coupling photolysis with ultrasound for degradation of IP has been developed. The photosonochemical decomposition rate constant is greater than the additive rate constants of the two processes. Degradation products were analysed by CG/MS performed in the electron-impact (EI) mode, at 70 eV potential using full scan mode. Degradation photoproducts were identified and a mechanism of degradation is proposed for two processes.